Exploring the comorbidity of personality disorder and musculoskeletal diseases among adults: a scoping review. (31st December 2021) - Quirk, Shae E.; Koivumaa-Honkanen, Heli; Kavanagh, Bianca E.; Honkanen, Risto; Heikkinen, Jeremi; Williams, Lana J.
Abstract: Background: There is growing evidence of comorbidities between mental disorders and musculoskeletal diseases (MSDs). However, personality disorder (PD) is often overlooked as a common type of mental disorder, and there has been no broad-level exploration or synthesis of their comorbidity with MSDs. The objectives of this review are to explore and understand the extent and type of evidence on the comorbidity of PD and MSDs among people aged ≥15 years and the burden associated with their comorbidity in clinical and population-based settings. Methods: The conduct of this review is guided by Arksey and O'Malley's methodological framework for scoping studies and the guidance published by the Joanna Briggs Institute (JBI). Peer-reviewed published and unpublished grey literature are eligible. Eligible study designs include cross-sectional, case-control, and cohort studies as well as existing reviews. A comprehensive search strategy was developed for Medline, CINAHL, and PsycInfo via EbscoHost. Protocols for data extraction and the presentation of the data including the descriptive synthesis adheres to the JBI methodological approach. Results: The main findings from this review will be presented including a discussion on what is known regarding the comorbidity of PD and MSDs and associated burden. In addition, we will highlight identified knowledge gaps and propose recommendations for future research. Conclusions: The findings from this review may highlight a need for routine psychiatric screening/assessment for PD in medical settings, to optimise treatment engagement, psychosocial recovery, and improve both mental and physical outcomes.